VD_FINDINFO Arrêt / 2016 / 237 vom 10. März 2016 - VD Tribunal cantonal (2016)
DÉCISION DE COTISATIONS ARRIÉRÉES, ACTIVITÉ LUCRATIVE DÉPENDANTE | 14 al. 1 LAVS, 16 al. 1 LAVS, 4 al. 1 LAVS, 5 al. 2 LAVS, 9 al. 1 LAVS